EXPERIMENTAL STUDY ON THE REALIBILTY TEST CALCINATION AND CARBONATION REACTIONS OF LIMESTONE ON CO2 ABSORPTION CAPACITY - Ryan Prabowo, Bagus
Cement is one of the most widely used construction materials in the world. Cement production accounts for approximately 7% of global greenhouse gas emissions. These emissions originate from the calcination process, which is the decomposition reaction of limestone (CaCO?) into calcium oxide (CaO) and carbon dioxide (CO?). The calcium looping technology is one of the technologies that can be used to reduce CO? emissions from cement production. This technology utilizes the calcination and carbonation processes to capture and store carbon dioxide (CO?). In the calcination process, limestone (CaCO?) is heated at high temperature to produce calcium oxide (CaO) and carbon dioxide (CO?). This study aims to assess the decline in the absorption capacity of CaO in the calcination-carbonation cycle for capturing CO? gas, as well as to compare the effectiveness of this cycle on limestone from various mining sources on fluidized bed reactor. The variation in CO? capture among samples from different mining locations was also observed, with limestone from some locations showing higher absorption capacity in the initial cycle but experiencing a faster decrease. Material characterization was conducted using X-Ray Diffraction (XRD) technique to analyze the changes in crystalline phase within the material after multiple cycles. Some samples showed the reappearance of calcite peaks after the calcination process, which is indicated to occur due to reactions with CO? from the air during cooling process. Microstructural changes were also observed using scanning electron microscope (SEM) testing technique, where some alterations in the microstructure of limestone (CaCO?) were noted. After five cycles, limestone from Padang, Tuban, Bayah, Cilacap, Citeureup, and Narogong are decreased in capacity of 41.66%, 21.25%, 31.19%, 25.00%, 30.97%, and 32.97%, respectively. The decrease in CO2 absorption capacity by CaO suggested causesd by cracking phenomenon in the material.